Thematic museums - Gao, Arthur (Hong Kong : Design Media Publishing Limited, 2012)
This book takes the architecture and display features of museums as its content, displaying various thematic museum features in modeling and space design. From the use of materials to their cultural and regional embodiment, the book analyses the cultural and historical connotations of museum design systematically.
engineering bookfair2016
Keywords: Museum buildings -- Designs and plans; Museum architecture -- Pictorial works